1988
DOI: 10.1172/jci113289
|View full text |Cite
|
Sign up to set email alerts
|

Iron chelation as a possible mechanism for aspirin-induced malondialdehyde production by mouse liver microsomes and mitochondria.

Abstract: To investigate the possibility that lipid peroxidation is the mechanism responsible for aspirin-induced liver damage, pure neutralized acetylsalicylic acid (ASA), 0.6-90.9 mM, was added to calcium-aggregated mouse liver microsomes followed by incubation in NADPH buffer at 370C for 60 min and subsequent measurement of malondialdehyde (MDA). MDA production at ASA concentrations from 1.2 to 4.6 mM was greater than control (P < 0.004). Peak MDA values were observed with 4.6 mM ASA, 39.58±6.73 nmol MDA/mg protein v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…However, Steer et al 13 affirmed that aspirin both in vivo and in vitro protects LDL (low-density lipoproteins) against subsequent oxidative modification, thereby providing an additional mechanism whereby aspirin may protect against atherosclerosis. Schwarz et al 12 reported that ASA intensifies MDA (malondialdehyde) production in hepatic microsomes and mitochondria. In our study we noticed that the TBARS concentration significantly increased in all investigated tissues of animals exposed both to F and ASA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Steer et al 13 affirmed that aspirin both in vivo and in vitro protects LDL (low-density lipoproteins) against subsequent oxidative modification, thereby providing an additional mechanism whereby aspirin may protect against atherosclerosis. Schwarz et al 12 reported that ASA intensifies MDA (malondialdehyde) production in hepatic microsomes and mitochondria. In our study we noticed that the TBARS concentration significantly increased in all investigated tissues of animals exposed both to F and ASA.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11] At present there are several scientific reports about the effect of ASA on antioxidant potential. [12][13][14] However, there does not appear to be any information available in the literature about interactions between F and ASA in soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…The formation, isolation, and characterization of an aspirin iron complex have also been reported during studies of oxidative damage to the liver mitochondria by aspirin, where the iron complex of aspirin was implicated in the toxicity [173]. In contrast, a mechanism of antioxidant action through the chelation of intracellular low-molecular-weight iron was proposed in cell studies, where aspirin has been shown to protect endothelial cells from oxidative stress damage caused by hydrogen peroxide [174]. Similarly, chelation of iron by aspirin has been suggested to be related to its antioxidant activity in the improvement of cataracts in diabetic models and other models of oxidative damage [175,176].…”
Section: Interactions Of Aspirin (Acetylsalicylic Acid) and Its Glucu...mentioning
confidence: 89%
“…This finding implies that it is the acetyl group within acetylsalicylic acid that confers the capacity to activate ferritin synthesis and that all other inhibitors of cyclooxygenase tested, including nonacetylated salicylate, do not fulfill the structural requirements necessary to activate ferritin translation. Aspirin has been demonstrated to specifically interact with and show affinity toward iron or iron complexes, 6,26 and it is therefore conceivable that aspirin accelerates dissociation of the ferritin repressor protein from ferritin mRNA, thus allowing ferritin translation. Clearly, more research is needed in order to further analyze the molecular mechanisms by which aspirin exerts its ferritin-inducing effect.…”
Section: Discussionmentioning
confidence: 99%